Harnessing digital technologies for triple bottom line sustainability in the banking industry: a bibliometric review - Megha Garg; Parveen Kumar (Future Business Journal)
Abstract The interconnection between the consequences of digital technologies and their impact on triple bottom line sustainability in the banking industry has emerged as a dynamic, multidisciplinary, and eclectic research area of global significance. Nevertheless, applying a systematic literature network analysis in this field has not yet been attempted. Therefore, this paper aims to investigate academic research by integrating different knowledge systems. To conduct this comprehensive analysis, this study employed the contextualized systematic literature review and bibliometric approaches method to make inferences from 154 publications obtained from the Scopus and Web of Science databases for the years 2012–2024 by using the biblioshiny tool. The study’s findings exhibited a noticeable upsurge in research trends in the last five years. With 64 publications, 2023 was the most productive year, and 2018 had the most influence with 188 citations. China, Italy, Spain, Egypt, and Malaysia were the most productive countries regarding citation performance. This study highlights the counterintuitive connection between digitalization, financial inclusion, sustainability, fintech, and sustainable development by providing support with recent literature to reflect the current developments in the field. The themes encountered here are crucial for regulators and practitioners who aim to capitalize on the mutually reinforcing nature of the two phenomena in the banking industry.